Increasing Public Legal Awareness of Land Certificate Ownership - Rangga Pamungkas, Muhammad Ilham; Djajaputra, Gunawan (Dinasti Research, 2024)
A land certificate is considered a legal land identity, providing authentic, inviolable proof of land control by the community. This certificate is an important piece of evidence in the legal realm, in accordance with the provisions stipulated in government regulations. The findings show that land certificates have high legal force, allowing them to be used in various financial transactions such as loans and credit. However, in Nagari Pasia Laweh, there are several factors that hinder the ownership of land certificates, including a lack of public understanding of the importance of land certificates and uncertainty regarding land ownership or transfer of ownership. Efforts are needed to increase civic knowledge and public legal awareness regarding ownership of land certificates. One of the efforts made is through outreach and the Complete Systematic Land Registration (PTSL) program. PTSL is a program that aims to provide legal certainty over land to the community at affordable costs, as well as to prevent land disputes and conflicts. Through socialization and the PTSL program, it is hoped that the community can increase awareness of the importance of owning land certificates as proof of land rights and maintaining the stability of land administration.